Trajnostni razvoj v Sloveniji - Kunčič, Aljaž (Teorija in praksa, 2024)
t. This article shows the significance of the sustainable development concept both globally and in Slovenia. It evaluates the country’s progress using various tools, focusing on the Sustainable Development Goals (SDGs). The article offers potential SDG progress simulations and introduces a method for pinpointing policies that could propel Slovenia to the forefront of global sustainable development. Emphasis is also placed on the importance of addressing the needs of the most vulnerable groups in these policy designs and on ways to identify them.
Keywords: cilji trajnostnega razvoja; človekove pravice; human development index; human rights; indeks človekovega razvoja; milenijski razvojni cilji; millennium development goals; Organizacija združenih narodov; ranljive skupine; sustainable development; sustainable development goals; Trajnostni razvoj; United Nations; vulnerable groups